Cash Flow Optimisation Strategies and Performance of Deposit Money Banks - Alao, Monisola Esther; Ifayemi, Olayinka (NIU Journal of Social Sciences; Vol 6 No 4 (2020): KIU Journal of Social Sciences, Vol. 6 No. 4, December 2020, 2021)
Banks encounter varying challenges in terms of competition which have effect on their competitive ability in meeting customer demands. The need to settle every obligation promptly necessitated the examination of Deposit Money Banksâ€™ cash-flow optimisation strategies and performance. Ex Poste research design and content analysis of 8 quoted Deposit Money Banks that published their financial statements between 2010 and 2018 were used. Panel regression on STATA analytical tool revealed that aggregate bank performance (ABP) indicated by ROE, ROA, Capital Adequacy, EPS and dividend. 1per cent increase in customer deposits will yield 57.9per cent increase in the performance of sampled banks while 1per cent increase in loans will yield significant decrease in bank performance. Overall R-square of the model showed that 36.2per cent variations in bank performance can be attributed to cash-flow optimisation variable. This affirms the importance of strategising cash-flow optimisation.  Keywords: Optimisation, Panel Regression, Performance, Quoted Banks, Strategy